The spesies composition and distribution pattern of Gastropod at Forrest Mangrove Block Bedul Segoro Anak, Alas Purwo National Park - Joko Swasono Adi; Sudarmadji Sudarmadji; Wachju Subchan (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2013)
This research aims to determine the spesies compossition and distribution pattern of Gastropod and its relationship with abiotic factors (pH, salinity, soil texture, and organic content of the soil, and the high of tide of the eustuary area) in the Mangrove forest at Blok Beduk Segoro Anak Alas Purwo National Park. This research was conducted on February 2013. Data was taken four times using a week time interval during one month. Every observation covered eight stations, where station 1 to station 4 consist of four transects and 40 plots, while station 5 to station 8 consist of 3 transects with 42 plots and each plot was 5 m × 5 m. Gastropod observed from each plot are preserved with 70% alcohol and identified in Malakologi Laboratory, Indonesian Institute of Sciences (LIPI). Results of the research reveated that the Gastropod observed consist of 19 families and 37 species, and the dominant family is Ceritidae. The Diversity index of Shanon Wiener was 0.53 (low deversity). Two available of Distribution pattern, group (Canarium labiatum, Cassidula nucleus, Cerithium coralium, Chicoreus brunneus, Cassidula vespertilionis, Cerithidea cingulata, Cerithidea quadrata, Chicoreus capucinus,Conus rattus, Conus striolatus, Ellobium aurisjudae, Littorina carinifera, Littorina scabra, Monodonta labio, Nassarius melanoides, Nassarius olivaceus, Nerita balteata, Nerita planospira, Nerita undata, Pugilina ternatana, Sphaerassiminea miniata, Telescopium telescopium, Terebralia sulcata, Thais intermedia), random (Angaria delphinus, Conus catus, Conus omaria, Cymatium moniliferum, Erronea errones, Oliva oliva, Polinices aurantius, Pollia undosa, Tectus pyramis, Trochus californicus, Turbo argyrostoma). The abiotic factors had relatianship not significantly (p = 0.067) on Gastropod distribution pattern. Keywords : Distribution pattern,Gastropod, species compossition